Daydream Continent: Europe as a Space-Time Horizon in Architectural History. Issue 1 (13th June 2018) - Castela, Tiago
Abstract : This article defends an attention to past meanings of 'Europe' as a prospective idea, focusing on the circulation of architectural ideas between European states and settler territories in late colonialism. It proposes research that questions the relation between present-day European architectural expertise and 'Europe' as a colonial space-time horizon. The latter term denotes how past colonial futures, understood as circulatory formations, entailed an imagination of social spaces that was never fully actualized, acting instead as a guiding device. Drawing on archival research in South Africa and in Mozambique, the article examines how during the Second World War architects in the region projected a 'European' space that, while being envisioned in contrast to an unequal non-European space, was not simply a propagation of coeval space-time in European cities. In addition, it notes how professional discourse in the 1960s articulated the hierarchies of development that structure the domain of Europeanness. However, the article does not stress the mere denunciation of 'Europe' as integral to colonial rationality, recalling instead the potential of prospective ideas as a form of open daydream.